2017
DOI: 10.1021/acschemneuro.7b00055
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructed Analogues of Bupropion Reveal Structural Requirements for Transporter Inhibition versus Substrate-Induced Neurotransmitter Release

Abstract: Bupropion (1), an α-aminophenone uptake inhibitor at plasma membrane transporters for dopamine (DAT) and norepinephrine (NET), is a widely prescribed antidepressant and smoking cessation aid. Cathinone (2), a structurally simpler α-aminophenone, is a substrate-type releasing agent at the same transporters and a recognized drug of abuse. Our goal was to identify the structural features of α-aminophenones that govern the mechanistic transition from uptake inhibition to substrate-induced release. Deconstructed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 25 publications
3
23
1
Order By: Relevance
“…In summary, the current study, coupled with out earlier investigations, 14,15 provides additional evidence that bulk around the terminal amine of phenylalkylamines such as amphetamine or cathinone (e.g. increasing chain length from NH to N-Me, to N-Et, to N- n -Pr, or to other bulky substituents as shown previously 14 ), and their optical isomers, dictate whether they will behave as MAT releasing agents or as MAT reuptake inhibitors.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…In summary, the current study, coupled with out earlier investigations, 14,15 provides additional evidence that bulk around the terminal amine of phenylalkylamines such as amphetamine or cathinone (e.g. increasing chain length from NH to N-Me, to N-Et, to N- n -Pr, or to other bulky substituents as shown previously 14 ), and their optical isomers, dictate whether they will behave as MAT releasing agents or as MAT reuptake inhibitors.…”
Section: Discussionsupporting
confidence: 74%
“…We have previously found that tertiary amine analogs of synthetic cathinones behave as DAT reuptake inhibitors, but the present and related studies (e.g. 14 ) show that secondary amine analogs of amphetamine and cathinone can also play this role if their alkyl-length or bulk is increased. N-Alkyl substituted phenylalkylamine analogs, and optical isomers thereof, also have a role in MAT selectivity/function and abuse liability as shown here (and before 14,15 ).…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations